Can clinical coordination be improved through Participatory Action Research (PAR) interventions?. (13th November 2019) - Vargas, I; Eguiguren, P; Mogollón-Pérez, A S; Samico, I; López, J; Bertolotto, F; De Paepe, P; Vázquez, M L
Abstract: Background: Despite the effectiveness of Participatory Action Research (PAR) in reducing the gap between evidence and practice, its use to improve care integration is rare. The aim is to analyze the factors influencing the implementation of PAR interventions to improve clinical coordination in public health services networks of Brazil, Chile, Colombia, Mexico and Uruguay. Methods: A qualitative, descriptive-interpretative study was conducted in participating healthcare networks of each country. Focus groups and individual semi-structured interviews were conducted to a criteria sample of participants: members of Local Steering Committee (LSC)(29), professionals' platform (PP)(28), other professionals (49) and managers(28). Thematic content analysis was performed, segmented by country and themes. Results: Findings reveal that contextual factors, the PAR process and interventions' content were determinants in the implementation, interacting over time, and differing among experiences. On the one hand, institutional support (providing the necessary resources) together with the interest of professionals and managers in participating, emerged as influencing factors influenced by other factors related to: the system (alignment with policies; electoral cycle), networks (lack of time due to work overload; precarious employment conditions) and individuals (limited mutual knowledge and mistrust). On the other, some characteristics of the PAR process facilitated institutional support and motivation: professionals' participation in all activities, design flexibility and shared decision-making - also present when interventions were based on mutual adjustment - the LSC's leadership and the facilitating role of the research team. Conclusions: Evidence is provided that when some contextual elements converge the implementation of interventions through PAR processes can turn into a factor of motivation and cohesion, determinant for the adoption of clinical coordination interventions. Key messages: Contributes to fill the knowledge gap in factors influencing the implementation of PAR interventions in healthcare. Provides a framework for analysis and recommendations for their implementation.